Application Of Shainin Methodology To Reduce Rejections In Spur Gear Manufacturing. (2018) - Khavekar, Rajendra; Vasudevan, Hari; Deshpande, Girish
Abstract: Today's manufacturing industries face complex challenges due to fluctuating customer demands and turbulent market place competition. In order to achieve the required quality level of a product at lower cost and to sustain in global market conditions, continuous improvement in manufacturing processes by reducing variations in processes is required. This study deals with one of the quality issues faced by an industry involved in Spur gear manufacturing, i.e.bore taper dimension variation 'Green Y', which is resolved by using Shainin methodology (Multi-Vari Chart). The small scale gear manufacturing unit is based in Mumbai, India. Spur gears are used in many mechanisms to transmit power at low running noise and at a high torque. Quality of the gear manufactured plays an important role during the power transmission using gears. During the manufacturing of gears, many defects occur and they are required to be diagnosed correctly for applying appropriate corrective measures, which otherwise could result in creation of new defects. Using Pareto analysis, defects with highest percentage of rejections were found. Shainin Multi-Vari Chart tool was used to identify the root cause. Multi-Vari tool is a powerful tool to reduce the list of suspect variables and to identify the root cause. Reduction of Spur gear bore dimension variation rejection from 6% (Average of three months) to 1.2% is achieved, resulting in a saving up to 15% cost of manufacturing. The rejection due to poor surface finish has also dropped from 0.7 to 0.25%. Further conclusion of the study also indicate that the Shainin methodology can be applied as an effective tool in quality management in small scale manufacturing industries.